Kind or contented? An investigation of the gift exchange hypothesis in a natural field experiment in Colombia - Francesco Bogliacino; Gianluca Grimalda; David Pipke (Kiel Institute for the World Economy (IfW), 2021)
The gift exchange hypothesis postulates that workers reciprocate above market-clearing wages with above-minimum effort. This hypothesis has received mixed support in dyadic employer-worker relationships. We present a field-experimental test to assess this hypothesis in the context of a triadic relationship in which only one out of two workers receives a pay increase. We conjecture that inequality aversion motivations may thwart positive reciprocity motivations and analyze the interaction between such motivations theoretically. Across three treatments, the pay increase is justified to workers based on either relative merit or relative need or was arbitrary as no justification was offered. Two conditions in which either none or both workers receive a bonus serve as the reference. In contrast to the gift exchange hypothesis, we find that pay increases lead to a decrease in productivity. Such a decrease is most sizable in the condition where both workers receive the bonus. A post-diction of this result is that workers interpret the monetary bonus as a signal of the employer's contentment with their effort, which makes them feel entitled to reduce their effort. In other treatments, receiving the pay increase while the coworker does not has a positive effect on productivity, especially when the pay increase is based on merit. This result is consistent with statusseeking preferences rather than aversion against advantageous inequality. Conversely, not receiving the pay increase while the coworker does, leads to lower productivity, especially when the pay increase is assigned based on relative needs.
Keywords: 330; Gift exchange; employer-worker relationship; pay inequality; field experiment; reciprocity; labor market; effort provision; fairness; wage inequality